Association of Complicated Diverticulitis With Development of De Novo Inflammatory Bowel Disease. Issue 7 (18th November 2020) - ur Rahman, Asad; Hussain, Ishtiaq; Hasan, Badar; ur Rashid, Mamoon; Tandon, Kanwarpreet Singh; Castro, Fernando
Abstract: Background: There has been a historic similarity in the epidemiology and pathophysiology of diverticular disease and inflammatory bowel disease (IBD). Because there are limited to no data on the role of diverticulitis as a potential risk factor for de novo IBD, we aimed to evaluate the role of diverticulitis and complicated diverticulitis as a potential predictor of IBD. Methods: We performed a retrospective, single-center study including patients older than age 18 years who were diagnosed with diverticulitis from January 2012 until December 2018 without a prior diagnosis of IBD. These patients were then evaluated for development of IBD. Univariate and multivariate analyses were conducted to compare the characteristics and outcomes between patients who did or did not develop IBD. Results: A total of 2770 patients were diagnosed with diverticulitis from 2012 until 2018. Of these patients, 17 were diagnosed with IBD, resulting in an incidence rate of 0.23% per patient-year. The incidence rate among patients who required surgery for diverticulitis was 0.44% per patient-year, and patients with complicated diverticulitis had an incidence rate of 0.91% per patient-year. Univariate analysis showed that the need for surgery related to diverticulitis (hazard ratio [HR], 6.27; P = 0.003) and complicated diverticulitis was associated with the development of IBD (HR, 14.71; P < 0.001). Multivariate analysis showed that complicated diverticulitis was the sole factor associated with IBD (HR, 10.34; P < 0.001). Conclusions: Patients with diverticulitis are at a higher risk of developing de novo IBD. This risk is highest in patients with complicated diverticulitis.